KEBEBASAN PENETAPAN MODAL DASAR PERSEROAN TERBATAS OLEH PARA PIHAK BERDASARKAN PERATURAN PEMERINTAH NOMOR 29 TAHUN 2016 - I Putu Wisnu Dharma Pura; I Nyoman Budiana (Universitas Pendidikan Nasional, 2018)
Along with the development of law and the community needs that developed rapidly, especially in the globalization era besides the enhancement of public demand for business development in accordance with good corporate governance principles, therefore on August 16, 2007 the Law No. 40 of 2007 was issued, which replace the Law Number 1 of 1995 concerning Limited Liability Companies. Then the enactment of Government Regulation No. 29 of 2016 concerning Changes in Authorized Capital of Limited Liability Company, specifically for beginner entrepreneurs to establish a Limited Liability Company. The provisions of Article 1 paragraph (3) of Government Regulation Number 29 of 2016 regulate: the amount of authorized capital for Limited Liability Company as referred to in paragraph (1) which based on the agreement of the Limited Liability Company founders. Furthermore, in Article 32 paragraph (1) of Law Number 40 Year 2007 concerning Limited Liability Company, regulate that the authorized capital of the Company is at least Rp. 50,000,000.00 (fifty million rupiah). From the above provisions it can be said, there is a norms conflict that cause multiple interpretations and does not provide legal certainty for the parties. Furthermore, the norms regulated in the Government Regulation should be in line with the norms regulated by the law above it, In this case Law Number 40 Year 2007.Keywords : Authorized Capital, Limited Liability Company, Parties